Development of comic page creator media based on Tumbuhkan, Alami, Namai, Demonstrasikan, Ulangi, Rayakan (TANDUR) learning for elementary school students - Nurul Hermiyati; Herlina Usman; Nurafiah Rizkiyani; Lilik Fitriani (Jurnal Bidang Pendidikan Dasar, 2023)
The demands of a teacher in this modern era in educating the nation's generation must be able to master IT to support effective learning activities. Data collection techniques used in this study were interviews, preliminary studies, observation, questionnaire collection, and documentation. This development research has gone through the validation stage with the acquisition of an average score of 96.36% from media experts with the criteria of "Very Eligible", material experts of 95% "very feasible", and linguists of 94.54% "very feasible" . In the limited trial the results were obtained, namely, for students at SDN Cikahuripan 01 the percentage of the questionnaire was 88% "very good" and SD Bojong Nangka 02 the percentage of the questionnaire was 90% with the "very good category". So that the comic page creator media based on TANDUR learning can be declared feasible to be tested on students.